Fostering Water Resilience in Brazil. - OECD. (Organization for Economic Cooperation & Development, 2022)
Brazil made significant progress in managing water resources since the adoption of the National Water Law in 1997 and the creation of the National Water and Sanitation Agency (ANA) in 2000. Nevertheless, water security challenges persist and will be aggravated by megatrends such as climate change, population growth, urbanisation, and the economic, social and environmental consequences of the COVID-19 pandemic.